Determinants of emotional distress in neonatal healthcare professionals: An exploratory analysis - Nazzari, Sarah; Grumi, Serena; Ciotti, Sabina; Merusi, Ilaria; Provenzi, Livio; Gagliardi, Luigi (Frontiers in Public Health, 2022)
Background. High levels of mental health problems have been consistently reported among neonatal healthcare professionals. While studies suggest that personality, coping strategies and safety culture might contribute to the psychological well-being of healthcare professionals, they have not been systematically investigated in low-risk (i.e., neonatal wards; NWs) and high-risk (i.e., neonatal intensive care units; NICUs) neonatal contexts. The current study investigated potential predictors of professionals’ emotional distress and whether they differ according to the work setting (i.e., NICUs vs NWs). Methods. Healthcare professionals (N=314) from 7 level-3 (i.e., NICUs) and 6 level-2 (i.e., NWs) neonatal units in Tuscany were included. Emotional distress (i.e., anxiety, depression, psychosomatic, post-traumatic stress symptoms and emotional exhaustion), Behavioral Inhibition System (BIS) and Behavioral Approach System (BAS) sensitivity, coping strategies and safety culture were assessed through well-validated, self-reported questionnaires. Results. Greater BIS/BAS sensitivity, avoidance coping strategies and a sub-dimension of safety culture (i.e., stress recognition) were all associated with greater risk of emotional distress, whereas job satisfaction emerged as a protective factor. Three specific profiles of professionals in term of personality, coping and safety culture were identified and further predicted emotional distress. Neonatal wards and NICUs personnel presented different associations between personality, coping and safety culture. Conclusions. These findings highlighted significant modifiable contributors of neonatal mental healthcare professionals’ well-being. Institutional initiatives that target these factors and, particularly, job satisfaction may promote professionals’ emotional well-being and thus improve caring processes.